Nature's Line George Goyder, surveyor, environmentalist, visionary. - Sheldrick, Janis (Wakefield Press, 2016)
Goyder was the first European explorer to see great salt lakes in the inland in flood and to witness the amazing transformation that follows the breaking of drought. When he attempted to adapt the pattern of settlement to climatic reality by defining the border of the zone of reliable rainfall, his warnings about the threat of drought were scorned.